High pressure X-ray emission spectroscopy at the advanced photon source. Issue 3 (2nd July 2016) - Xiao, Yuming; Chow, Paul; Shen, Guoyin
ABSTRACT: The structural, electronic, and magnetic properties of materials under high pressure are of fundamental interest in physics, chemistry, materials science, and earth sciences. Among several hard X-ray-based techniques, X-ray emission spectroscopy (XES) provides a powerful tool to probe element-specific information for understanding the electronic and magnetic properties of materials under high pressure. Here, we discuss on the particular requirements and instrumentation used in high pressure XES experiments. We then present several examples to illustrate the recent progress in high pressure XES studies at the Advanced Photon Source, followed by an outlook toward future development in high pressure XES.